PROBLEMATIKA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 DI SMA DHARMA PRAJA DENPASAR - Wahyuningsih, Kompyang Sri (PANGKAJA: JURNAL AGAMA HINDU, 2021)
The purpose of this study was to analyze the problems of online learning during the Covid-19 pandemic and the solutions to solve them at SMA Dharma Praja Denpasar. This type of research is a case study or field research using primary data sources obtained through direct interviews by following health protocols. In addition, data is also obtained through library research using secondary data sources collected through textbooks, e-books, laws and regulations, websites, and other sources relevant to the research problem. The research data were analyzed qualitatively with an interactive model, which consists of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of online learning during the Covid-19 pandemic at Dharma Praja Denpasar High School has various problems, both from teachers, students and parents of students. The problems of the teacher are in the form of weak mastery of IT and limited access to supervision of students, from students, namely lack of motivation and concentration in learning, limited support facilities, internet network access, while from parents in the form of limited time to accompany their children during online learning. These various problems can be overcome by increasing competence in the use of IT, giving simple tasks, intensive supervision by involving parents.